Francis A. Sullivan, S.J. and ecclesiological hermeneutics : an exercise in faithful creativity - Canaris, Michael M. (Brill's studies in Catholic theology, 2016)
In 'Francis A. Sullivan, S.J. and Ecclesiological Hermeneutics', Canaris traces the significant contributions that Francis A. Sullivan, S.J. has made to Catholic ecclesiology, paying particular attention to the method and application of his hermeneutical approach to the writings of the magisterium. Though highly esteemed by professional theologians in both Catholic and ecumenical circles, Sullivan is less well-known among general audiences than many of his peers. The author addresses this lacuna by arguing that Sullivan's work, when viewed through an interpretive lens, can aid the faithful to engage seriously with magisterial texts of various genres and levels of authority, find meaning within them, and encourage an active reception process whereby contemporary understanding of the teaching (and learning) role of the entire church becomes possible.